2020
DOI: 10.1038/s41598-020-61062-7
|View full text |Cite
|
Sign up to set email alerts
|

Attention and cardiac phase boost judgments of trust

Abstract: Fluctuations in mental and bodily states have both been shown to be associated with negative affective experience. Here we examined how momentary fluctuations in attentional and cardiac states combine to regulate the perception of positive social value. faces varying in trustworthiness were presented during a go/no-go letter target discrimination task synchronized with systolic or diastolic cardiac phase. Go trials lead to an attentional boosting of perceived trust on high trust and ambiguous neutral faces, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 61 publications
3
7
0
Order By: Relevance
“…A total of 35 volunteers (age: M = 22.6 years, SD = 3.4; 27 females) were recruited via the departmental subject pool. Calculations in G*Power (Version 3.1;Faul et al, 2007), based on a previous study of cardiac gating on emotional valence (Garfinkel et al, 2014), indicated that a sample size of 35 would be needed to obtain an effect size (f 2 ) of .40 at a power of 85% with an α of .05, which is consistent with other studies in the field (Azevedo et al, 2018;Li et al, 2020). The study was approved by the Royal Holloway University of London Department of Psychology ethics committee, and written informed consent was obtained from all participants.…”
Section: Methodssupporting
confidence: 80%
See 1 more Smart Citation
“…A total of 35 volunteers (age: M = 22.6 years, SD = 3.4; 27 females) were recruited via the departmental subject pool. Calculations in G*Power (Version 3.1;Faul et al, 2007), based on a previous study of cardiac gating on emotional valence (Garfinkel et al, 2014), indicated that a sample size of 35 would be needed to obtain an effect size (f 2 ) of .40 at a power of 85% with an α of .05, which is consistent with other studies in the field (Azevedo et al, 2018;Li et al, 2020). The study was approved by the Royal Holloway University of London Department of Psychology ethics committee, and written informed consent was obtained from all participants.…”
Section: Methodssupporting
confidence: 80%
“…These effects highlight how signals from the heart bias the social judgments we make, providing a first mechanistic account of how bodily states influence social evaluations and first impressions. though a recent study found that in conditions of high attentional load, people tend to judge faces presented during systole as less trustworthy than those presented at diastole (Li et al, 2020), it remains unclear to what extent the modulation of social judgments is dependent on cardio-visual synchrony or phasic signals of bodily arousal.…”
Section: Statement Of Relevancementioning
confidence: 99%
“…Many studies in the last decade have confirmed the robustness of this effect across a wide range of RSVP and background stimuli, as well as in tests of perceptual learning, tilt aftereffect, STM, long-term memory, and source memory. Detecting an RSVP target not only affects perceptual processing and memory, but also increases preferences for food items, faces, and other visual images presented concurrently with the target (Bakkour et al, 2016; Li et al, 2020; Salomon et al, 2018; Schonberg et al, 2014). Pupillometry and functional imaging studies suggest that target detection may induce a phasic response in neurons in the Locus Coeruleus, producing a temporally specific, but spatially broad enhancement across many regions of the brain (Swallow et al, 2012, 2019; Yebra et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Though LC activity drives changes in pupil size, pupil size ultimately reflects the combined effects of several neuromodulatory systems and subcortical structures (Larsen and Waters, 2018), is correlated with activity throughout the brainstem (de Gee et al, 2017), and can produce correlation maps that differ from those produced by LC activity (Turker et al, 2021). Furthermore, studies examining the relationship between the ABE and cardiovascular activity, which suppresses LC activity during the systole phase of the cardiac cycle, have provided mixed results (Li et al, 2018(Li et al, , 2020.…”
Section: Evidence That the Abe Is Tied To Phasic Lc Activitymentioning
confidence: 99%
“…Another possibility explored in the literature is whether the ABE enhances memory by modifying the perceived value of items that appear with targets relative to distractors. Pairing an image with a target cue rather than a distractor cue increases its perceived value (cued approach; Schonberg et al, 2014), leading to a willingness to pay more for it, greater liking and trust ratings for faces, and greater wanting ratings for objects (Swallow and Atir, 2018;Li et al, 2020;Botvinik-Nezer et al, 2021). This raises the possibility that the ABE is due to changes in the perceived value of target-paired items (cf.…”
Section: Temporal Selection May Also Directly Enhance Episodic Memorymentioning
confidence: 99%